Personalised Communicative Ecologies: The role of social media in the Bersih movement’s mobilisation - Ngu, Ik Ying (Curtin University, 2021)
This thesis uses Foth and Hearn’s (2007) notion of ecology to examine how the Bersih movement uses social media to mobilise individuals through personalised conversations. It analyses the interaction between citizens within an ecology to capture their pattern of media usage and political discourse within the context of electoral reform in Malaysia between 2017 and 2020. The findings show citizens’ personal expressions and self-fulfillment are becoming more centralized within the Bersih movement.